Rare bird documentation form for Northern Goshawk at Hanover Township in Allamakee County, 1982 - Robinson, John C., 1959-et al (1982)
Rare bird documentation form for a Northern Goshawk at Hanover Township in Allamakee County, IA on November 21, 1982. Epson - sheet feed